Groundwater Quality and Irrigation Suitability Assessment Using Geochemical and GIS-Based Approaches in Arid Regions - Radhi, Noor A.; Al-Madhhachi, Abdul-Sahib T.; Sachit , Dawood E. (Civil Engineering Journal, 2025)
In arid and semi-arid climates, such as Iraq's Salah Al-Din Governorate, the availability of surface water is much lower than demand, so groundwater becomes a vital resource. Groundwater is one of the basic needs for agricultural irrigation, and therefore this study presents a suitable groundwater suitability assessment for agricultural irrigation based on a comprehensive assessment of groundwater geochemical properties and spatial distribution using the kriging technique within Geographic Information Systems (GIS). Key water quality parameters, including EC, TDS, pH, Cl⁻, Na⁺, K⁺, NO₃⁻, HCO₃⁻, CO₃²⁻, SO₄²⁻, Ca²⁺, and Mg²⁺, were determined in a total of 51 wells across the study area. In addition, two wells located in the Al-Alam District of Salah Al-Din Governorate were remeasured in 2025 to assess changes in water levels. These measurements were compared to the static water levels recorded in 2014 for one well and in 2008 for the other. To determine irrigation suitability, the Water Quality Index, Sodium Adsorption Ratio, Residual Sodium Carbonate, and Total Hardness were calculated and analyzed. Groundwater quality was spatially variable, but several areas exceeded the FAO limits for safe agricultural use at all groundwater depths considered owing to salinity, sodicity, and anthropogenic contamination. Spatial mapping using GIS identified the risk zones and assisted in recommending appropriate management practices for sustainable groundwater development. Such findings emphasize the importance of regular monitoring together with appropriate irrigation management and remediation measures to reduce groundwater degradation and maintain agricultural development in Salah Al-Din Governorate.